Electrophoretic analysis of some Lathyrus L. species based on seed storage proteins - Emre, Irfan (Springer, 2009)
Present study reported the variation in electrophoretic seed subfraction (albumins, globulin A, globulin B, glutelins) patterns in some Lathyrus species collected from their natural habitats different localities in Turkey. Electrophoretic data were documented by using a gel documentation system (Bio-Rad, USA) and analysed by using Quantity 1-D analysis software and also the dendograms were formed with 4.0% tolerance in UPGAMA (Unweighed Pair-Group Arithmetic Mean). The differences among species were observed and all seven species were clearly identifiable from the protein patterns. The dendograms obtained from cluster analysis of seed storage proteins data showed examined species have displayed a number of distinct relationships. According to our results, it seems justified to recommend a wider use of electrophoretic analysis of seed storage proteins in taxonomic investigations of leguminous plants.
Keywords: Cluster analysis; Lathyrus; Molecular taxonomy; SDS-PAGE; Seed storage proteins